Influence of road incline and body position on power-cadence relationship in endurance cycling - Emanuele, U.; Denoth, J. (European Journal of Applied Physiology, 2012)
In race cycling, the external power-cadence relationship at the performance level, that is sustainable for the given race distance, plays a key role. The two variables of interest from this relationship are the maximal external power output (P max) and the corresponding optimal cadence (C opt). Experimental studies and field observations of cyclists have revealed that when cycling uphill is compared to cycling on level ground, the freely chosen cadence is lower and a more upright body position seems to be advantageous. To date, no study has addressed whether P max or C opt is influenced by road incline or body position. Thus, the main aim of this study was to examine the effect of road incline (0 vs. 7%) and racing position (upright posture vs. dropped posture) on P max and C opt. Eighteen experienced cyclists participated in this study. Experiment I tested the hypothesis that road incline influenced P max and C opt at the second ventilatory threshold (P VT²/max and C VT²/opt). Experiment II tested the hypothesis that the racing position influenced P VT²/max, but not C VT²/opt. The results of experiment I showed that C VT²/opt and P VT²/max were significantly lower when cycling uphill compared to cycling on level ground (P < 0.01). Experiment II revealed that P VT²/max was significantly greater for the upright posture than for the dropped posture (P <0.01) and that the racing position did not affect C VT²/opt. The main conclusions of this study were that when cycling uphill, it is reasonable to choose (1) a lower cadence and (2) a more upright body position.